Optimizing the handling of the COVID-19 national disaster through vaccination in Magelang Regency - Diesyana Ajeng Pramesti; Teara Noviyani Sekar Melati; Praba Setiya Safitri; Tri Indah Nugraheni; Agus Ismanto; Eky Rizky Prasetya (Universitas Muhammadiyah Magelang, 2022)
The government has designated the Covid-19 pandemic as a national disaster that has become a major concern since its emergence. The Covid-19 disaster has an impact on various sectors, ranging from the education, health to the economic sector. One of the government's efforts to overcome this national disaster is to organize free and safe vaccinations. The Unimma community service team also contributes and collaborates with other agencies to realize the government's vaccination program and create a healthy community that is ready to return to normal activities, so that all affected sectors can recover. This program is also a form of concern for others which aims to reduce the health crisis that has occurred in Indonesia over the past two years due to the Covid-19 pandemic. This activity was carried out with the Magelang District Health Office and the Puskesmas in 5 stages. The results obtained in this program are the implementation of the first and second doses of vaccines as well as data on vaccine recipients.